Nitrogen fertilization-induced acidity and suitability of δ13C to study the dynamics of soil inorganic carbon in agroecosystems - Mostafa Abdollahpour; Dennis Hollemann; Leopold Sauheitl; Georg Guggenberger; Kazem Zamanian (Geoderma)
Neutralization of soil inorganic carbon (SIC), i.e., dissolution of carbonate minerals caused by N fertilization-induced acidity, is an ongoing reaction in agroecosystems that leads to significant contribution of SIC to soil CO2 emission. Analyzing δ13C natural abundance of the emitted CO2 is commonly used to quantify the contribution of SIC in total CO2 emission. However, carbonates recrystallization in isotopic equilibrium with soil respiration can lead to miscalculation, where despite detecting δ13C signal from carbonates in the emitted CO2, the SIC stock may not necessarily change. We tested the effects of ammonium sulfate, urea, chicken manure, liquid pig manure and no fertilization (i.e. control) on soil carbonates neutralization and the contribution of SIC in total CO2 emission over a 21 day incubation experiment. The alkali trap method was used to measure the total CO2 emission and the isotopic composition of carbon (C) in the emitted CO2 from the soil. Liquid pig manure followed by ammonium sulfate apparently led to the highest cumulative SIC-originated CO2 emissions, while chicken manure and urea showed equally the smallest amount. Nitrate can support the estimation of SIC-originated CO2 emission when nitrification is the only source of soil acidification. Dissolved Ca2+ concentration was a more robust proxy than NO3- for quantification of SIC-originated CO2 emission in our batch experiment, however, more evidences have to be collected before using Ca2+ as a proxy in open soil systems. Verification of the δ13C values by dissolved Ca2+ showed that the contribution of SIC to the total CO2 emission is overestimated after organic N fertilization, whereas an underestimation in the contribution of SIC to the soil CO2 emission was observed after inorganic N fertilization. In summary, the δ13C analysis could yield inaccurate results regarding the effects of N fertilization on the contribution of SIC in soil CO2 emission which should be considered in the future studies. From an environmental point of view, it can be concluded that when the amounts of N, especially in ammonium form e.g. amino groups are relatively high in organic fertilizers as it was the case in liquid pig manure compared to inorganic fertilizers, organic and inorganic N fertilizers lead to comparable amounts of SIC loss. This should be considered in applying organic fertilizers as a sustainable strategy to slow down the rate of soil acidification.